Screening of syphilis using rapid plasma reagin test in apparently healthy population in Madhya Pradesh: a 6 years study - Jain, Savita Bharat; Ranjan, K. P.; Gandhi, Shashi (International Journal of Advances in Medicine, 2017)
Background: To analyze the prevalence of syphilis in apparently healthy population in Madhya Pradesh during last 6 years. Methods: Serum samples were collected from Departments of Obstetrics and Gynecology, Skin and Venereal diseases, Medicine, Surgery, etc., of the period of 6 years. All the serum samples were screened for syphilis by rapid plasma reagin (RPR) test using standard methods. Results: Out of 21,742 samples, 133 (0.62%) serum samples were found to be positive. The highest seroprevalence was observed in the group aged 25-31 years (0.89%) and lowest in 18-24 years (0.31%). Conclusion: RPR testing in this populations group plays a special value in the diagnosis, treatment and prevention of syphilis.